Servant Leadership, Service Management Support, and Digital Literacy as Determinants of Teacher Performance - Yohanes Paulus Manubura; Ronald Suryaputra; Dany M. Handarini (Journal of Educational Management Research, 2026)
This study aims to examine the influence of principals’ servant leadership, service management support, and teachers’ digital literacy on teacher performance. A quantitative approach was employed using a survey method. The study involved 40 teachers selected through a saturated sampling technique. Data were collected through a structured questionnaire distributed via an online form, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the SmartPLS application. The findings indicate that principals’ servant leadership and service management support have positive but statistically insignificant effects on teacher performance. In contrast, teachers’ digital literacy has a positive and significant effect on teacher performance and emerges as the most dominant variable in the research model. Simultaneously, the three independent variables contribute to teacher performance, with digital literacy playing the most substantial role. These results suggest that teacher performance in contemporary educational environments is more strongly influenced by teachers’ individual competencies in utilizing digital technologies than by leadership and managerial support alone. Therefore, strengthening teachers’ digital literacy should become a strategic priority in efforts to improve teacher performance in schools.